Temporal water mobility and sodium intensity measurements in penumbra and core tissue during acute stroke - (:unkn) unknown (My University, 2011)
The perfusion-diffusion mismatch is a commonly used approach to distinguish between still-viable penumbra and irreversibly damaged core tissue in human stroke patients. However, in recent years it has become clear that the diffusion lesion does not accurately identify infarcted tissue, casting doubt on the validity of the perfusion-diffusion mismatch approach. Sodium-MRI (Na-MRI) can offer an alternative approach to identifying tissue at risk of infarction. The aim of this study was to investigate the hypothesis that an increase in 23Na signal above normal levels indicates tissue destined for infarction [1]. To do this, the timecourse evolution of Apparent Diffusion Coefficient (ADC) and 23Na signal changes during the acute phase of a rodent stroke model was measured, differentiating between penumbral and core tissue through the use of both the perfusion deficit measured immediately before the animals were sacrificed (~5hrs after stroke) and the subsequent histologically-determined regions of infarcted tissue.
International Society for Magnetic Resonance in Medicine
PUBLISHED
Montreal
Keywords: Sodium-MRI; Stroke; Penumbra; Neuroscience; Next Generation Medical Devices